Kinerja Pegawai Ditinjau dari Perilaku Cyberloafing dan Komitmen Organisasi - Rika Wahyuni; Hadi Irfani; Rina Mariana (Psyche 165 Journal, 2020)
The aim of this study was to determine the influence cyberloafing behavior and organizational commitmenton employee performance. This research is a quantitative research with a descriptive approach, respondents surveyed in this study amounted to 101 employees of the Padang City Department of Educationby saturated sampling technique.Then carried out analysis to the data obtained by using multiple linear regression analysis. The results found: (1) cyberloafing behavior has a negative and significant effect on employee performance, (2) organizational commitment has a positive and significant effect on employee performance and (3) cyberloafing behavior and organizational commitment simultaneously has a significant effect on employee performance. The contribution of cyberloafing behavior and organizational commitment on employee performance amounted to 65.2%. Where as the remainder about 34.8% described by other variable is not used within this research.